Inequality, education and democracy in Africa - (:unkn) unknown (My University, 2022)
The question of the links between inequality and democracy is still the subject of an intense academic debate. In this paper, we revisit this issue by explicitly taking into account the interactions between education and inequality to measure their concomitant impact on democracy in Africa. Specifically, we estimate a linear model using the GMM technique in a dynamic panel on a sample of 30 African countries over the period 1990-2019. It turns out, in line with modernization theory, that the level of wealth of a country positively impacts democratization. Moreover, inequality negatively impacts the level of democracy. However, this impact is mitigated by the level of education: above a certain level of education, inequality positively impacts democratization. Similarly, education negatively impacts democratization. Nonetheless, the greater the inequality in a country, the more this effect will be attenuated until it becomes positive and thus education fosters democratization beyond a certain threshold of inequality.
Keywords: African Research